KESESUAIAN PELAKSANAAN PEREMAJAAN KELAPA SAWIT MELALUI PROGRAM PEREMAJAAN KELAPA SAWIT RAKYAT (PSR) (Studi Kasus: KUD Tunas Muda Kabupaten Siak-Riau) - Pipin Dwi Astiti Asti; A. Faroby Falatehan; Eka Intan Kumala Putri (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2022)
The decision to replant oil palm is a complex decision for smallholder farmers in Teluk Merbau Village who are members of the Tunas Muda KUD, Siak Regency, Riau Province. Oil palm replanting needs to be done because the age of oil palm plantations for KUD Tunas Muda farmers on average has reached a planting age of >30 years with a production yield of only 1.47 tons per hectare per year. The implementation of oil palm replanting is carried out through the People's Palm Oil Rejuvenation (PSR) program. This research aims to examine the applicable regulations regarding the implementation of oil palm replanting at KUD Tunas Muda and analyze the perception of smallholder farmers on the implementation of oil palm replanting. Data were analyzed using gap analysis and qualitative descriptive analysis. Adjusted to the Director General of Plantation Decree No.29/KPTS/KB.120/3/2017 concerning guidelines for the implementation PSR. The results of the analysis of the perception farmers indicate input aspects, financial aspects and institutional aspects that influence farmers' decisions in the implementation of oil palm rejuvenation. The stakeholder involvement aspect consists of 3 components: related stakeholders, stakeholder rights and stakeholder obligations. The implementation PSR program is very helpful and this program can only be accepted by oil palm farmers who are members of the Tunas Muda KUD membership.